2012
DOI: 10.1007/s13320-012-0062-7
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon resonance based sensing of different chemical and biological samples using admittance loci method

Abstract: The admittance loci method plays an important role in the design of multilayer thin film structures. In this paper, admittance loci method has been explored theoretically for sensing of various chemical and biological samples based on surface plasmon resonance (SPR) phenomenon. A dielectric multilayer structure consisting of a Boro silicate glass (BSG) substrate, calcium fluoride (CaF 2) and zirconium dioxide (ZrO 2) along with different dielectric layers has been investigated. Moreover, admittance loci as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…7 shows surface plasmon resonance momentum matching condition with three different prism materials namely ceramic, SF6 and SF2 at 670 nm wavelength. The intersections of curves correspond to propagation constant of incident light and propagation constant of surface plasmon wave which satisfy (6). From phase matching condition as shown in (6), it can be concluded that for a fixed surface plasmon active metal film and a fixed dielectric sample, there exists an inverse relationship between prism material refractive index and surface plasmon resonance angle.…”
Section: Simulated Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…7 shows surface plasmon resonance momentum matching condition with three different prism materials namely ceramic, SF6 and SF2 at 670 nm wavelength. The intersections of curves correspond to propagation constant of incident light and propagation constant of surface plasmon wave which satisfy (6). From phase matching condition as shown in (6), it can be concluded that for a fixed surface plasmon active metal film and a fixed dielectric sample, there exists an inverse relationship between prism material refractive index and surface plasmon resonance angle.…”
Section: Simulated Resultsmentioning
confidence: 98%
“…The first application of plasmonic phenomenon as a sensing tool was observed in gas detection and biosensing [1]. Admittance loci method has been used in thin film modeling [2] and design of plasmonic structures [3][4][5][6]. Investigation on surface plasmon sensor comprising of high refractive index transparent ceramic prism material for improved sensitivity has been reported [7].…”
Section: Introductionmentioning
confidence: 99%
“…Surface plasmon excitation in the infrared region involves the use of chalcogenide 5 and silicon as coupling prism materials. 19,20 Gupta et al have worked on tuning and sensitivity enhancement of an SPR sensor. A work on modeling of chalcogenide glass based SPR sensor for chemical sensing using near-infrared light has been reported earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Admittance loci method has been used in thin film modeling [8] and design of SPR based devices [9][10][11][12]. Prism material dependency as well as sensing application of SPR based on admittance loci analysis has been reported earlier [13,14]. Gupta and Kondoh have worked on tuning and sensitivity enhancement of SPR sensor [15].…”
Section: Introductionmentioning
confidence: 99%